Impact of Antibiotic Policy in a Tertiary Care Research Institute Hospital in Egypt: Three Years Experience - Badawi, Hala; Saad Diab, Manal; El Said, Manal (International Journal of Infection Control, 2007)
IntroductionThe main forces driving the increase in antimicrobial-resistant bacteria are poor infection control practices and inappropriate use of antibiotics. Once these factors are addressed, specific antibiotic utilization strategies may help decrease or prevent the emergence of resistance. These strategies include antibiotic restriction, combination therapy, and antibiotic cycling. Dependence on one class of antibiotic to treat a population, despite optimal dosing and duration of treatment, may allow for the selection of resistant organisms within that population. Cycling, or rotating antibiotics within or between classes, by altering the selective pressure for bacteria to develop resistance to any particular antibiotic, may be an important component, from a population perspective, of antimicrobial stewardship. An antibiograms is particularly helpful for choosing empiric and pathogen-directed treatment regimens. It also assists in antibiotic "streamlining", the process by which excessively broad-spectrum empiric antibiotic therapy can be switched to narrower spectrum therapy aimed only at the implicated pathogen(s). It must be acknowledged that an antibiogram-based guideline does not have an unlimited duration of utility. It is likely that shifts in antibiotic usage engendered by the creation of the guideline will, over time, lead to a change in resistance patterns. Thus, it is prudent to update antibiograms and antibiogram-based antibiotic guidelines on a regular basis. Antibiotic cycling involves the deliberate removal of the antimicrobial of choice to treat a particular infectious syndrome in a specific unit with the intention of reintroducing that antimicrobial at a predetermined time in the future. Several antibiotics are commonly rotated in this fashion. Cycling takes advantage of the observation that resistance to a particular antimicrobial decreases when that antimicrobial is no longer used. In addition to restriction, antibiotics are rotated to maintain or promote antibiotic heterogeneity in order to alter the selective pressures present and thus prevent the emergence of resistance to any particular antibiotic. Community prescribing practices have been shown to influence rates of resistance in common bacterial pathogens, and long-term–care facilities are increasingly being recognized as reservoirs for antibiotic-resistant pathogens. Antimicrobial resistance in S. aureus emerged soon after penicillin came into common use in the 1940s. During the next 2 decades, resistance of this pathogen to penicillin became widespread, followed by increasing resistance to the new semisynthetic penicillinase-resistant antimicrobial drugs (e.g., methicillin, oxacillin, nafcillin). In the last 20 years, methicillin-resistant S. aureus (MRSA) has spread throughout the world in healthcare settings. In addition, serious MRSA infection has been increasingly reported in persons without identified predisposing risk, including recent healthcare exposure. Members of the family Enterobacteriaceae producing beta-latamases constitute a serious threat to current beta-lactam therapy. In addition, guidelines of the National Committee for Clinical Laboratory Standard (NCCLS)6 suggest that confirmed extended spectrum beta-lactamase (ESBL) producing strains should be reported as resistant to all penicillins, cephalosporins and aztreonam. MRSA and ESBL infections have been increasing at an alarming rate world-wide over the past two decades. They are responsible for nosocomial infections and adverse patient outcomes. Numerous reports describe nosocomial outbreaks in various countries.These infections may be life-threatening and cause considerable morbidity as they are of special concern for several reasons. They are associated with prolonged hospitalization and increased costs with few therapeutic options. These multidrug-resistant bacteria (MRB) increasingly have spread from hospital settings to noninstitutional environments.On the other hand, prolonged MRSA carriage was found to occur after hospital discharge increasing the infection by this organism in both community and hospital settings. Transmission of such infections occurs primarily from colonized or infected patients to other patients or staff and vice versa mainly through transiently-colonized hands of healthcare personnel. The environment also contributes to such transmission. In our institute hospital, a surveillance study in 2004 showed that MRSA and ESBL represented 11.9% and 29.9% of nosocomial infections respectively. This triggered us to implement an antibiotic policy with cycling and follow up.